The impact of anxiety-management strategies on EFL students’ anxiety levels and vocabulary acquisition - Eliana Pinza-Tapia; Paul Gonzalez-Torres; Jimmy A. Aleman; Karla V. Romero (Institute of Advanced Engineering and Science, 2026)
Foreign language anxiety (FLA) remains a significant barrier to vocabulary acquisition in English as a foreign language (EFL) classroom, particularly among young learners who fear negative evaluation, public speaking, and academic failure. Although the relationship between anxiety and poor lexical performance is well established, limited research has examined how coordinated classroom-based anxiety-management strategies influence both vocabulary development and students’ emotional experiences within regular instructional practice. This mixed-methods study examined the impact of six anxiety-management strategies implemented over six weeks with 50 A1-level secondary EFL students in Ecuador. The intervention integrated lengthened wait time, improved questioning techniques, acceptance of varied responses, peer collaboration, content-focused instruction, and positive teacher–student relationships into vocabulary lessons. Data were collected through an adapted anxiety scale, pre- and post-tests, questionnaires, interviews, and classroom observations. Results revealed a statistically significant improvement in vocabulary scores, with a large effect size, alongside increased confidence, participation, and engagement. Strategies fostering psychological safety, particularly content-focused instruction, peer collaboration, and strong teacher–student rapport, were perceived as most effective. The findings suggest that integrating affective support with cognitive scaffolding is associated with reduced anxiety-related behaviors and enhanced vocabulary development, positioning anxiety management as a central component of effective EFL pedagogy rather than a supplementary practice.